1999
DOI: 10.1037/0882-7974.14.2.314
|View full text |Cite
|
Sign up to set email alerts
|

The locus of adult intelligence: Knowledge, abilities, and nonability traits.

Abstract: Some intelligence theorists (e.g., R. B. Cattell, 1943; D. O. Hebb, 1942) have suggested that knowledge is one aspect of human intelligence that is well preserved or increases during adult development. Very little is known about knowledge structures across different domains or about how individual differences in knowledge relate to other traits. Twenty academic and technology-oriented tests were administered to 135 middle-aged adults. In comparison with younger college students, the middle-aged adults knew mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
3
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 37 publications
(78 reference statements)
8
114
3
3
Order By: Relevance
“…It should be noted that, although older people showed impaired performance on the People Pieces Analogy task, this task does not test crystallized intelligence and semantic knowledge, which appear to be relatively preserved with age (Ackerman & Rolfhus, 1999;Lindenberger & Baltes, 1997). Rather, the task used in the current study taps fluid intelligence, which has been shown to decline with age (Isingrini & Vazou, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, although older people showed impaired performance on the People Pieces Analogy task, this task does not test crystallized intelligence and semantic knowledge, which appear to be relatively preserved with age (Ackerman & Rolfhus, 1999;Lindenberger & Baltes, 1997). Rather, the task used in the current study taps fluid intelligence, which has been shown to decline with age (Isingrini & Vazou, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Control beliefs and self-efficacy predict cognitive performance and activities, but they are only one part of a larger set of interrelated traits and attributes that predict activities and cognition and that could account for cognitive-enrichment effects (e.g., Ackerman & Rolfhus, 1999). For example, recent research indicates that goal setting and planning are also important for initiating and maintaining physical-exercise routines (e.g., Armitage & Conner, 2000;Huang, Lee, & Chang, 2007;Scholz, Sniehotta, Schuez, & Oeberst, 2007).…”
Section: Positive Attitudes and Beliefsmentioning
confidence: 99%
“…Individuals select particular areas in which they invest time, energy, and cognitive resources to gain knowledge and experience (Ackerman, 2000;Ackerman & Rolfhus, 1999;Baltes, 1997;Beier & Ackerman, 2005;Cattell, 1971). Some aspects of cognitive function, particularly those heavily imbued with knowledge or experience (what Baltes, 1997, refers to as the pragmatics of cognition), will be relatively well preserved in adulthood, provided that the performance context does not introduce performance-specific constraints due to challenges to impaired processing mechanisms (e.g., Hertzog, 1989).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Age-related growth in pragmatics and knowledge-based systems is evident in verbal intellectual functions, as well as in world knowledge and acculturation, and particularized knowledge systems that grow as a function of one's choice of engagement (Ackerman & Rolfhus, 1999;Hoyer, Rybash, & Rooodin, 1989;Schaie, 1994;Stanovich, West, & Harrison, 1995). There appears to be a reciprocal relationship between ability and discourse processing.…”
Section: The Nature Of Cognitive Agingmentioning
confidence: 99%